2017
DOI: 10.1192/bjp.bp.116.190058
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and moderators of treatment outcome in patients receiving multi-element psychosocial intervention for early psychosis: Results from the GET UP pragmatic cluster randomised controlled trial

Abstract: The GET UP multi-element psychosocial intervention proved to be superior to treatment as usual in improving outcomes in patients with first-episode psychosis (FEP). However, to guide treatment decisions, information on which patients may benefit more from the intervention is warranted.To identify patients' characteristics associated with (a) a better treatment response regardless of treatment type (non-specific predictors), and (b) a better response to the specific treatment provided (moderators).Some demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…What little is so far known has been gathered from services already offering a broader EIP service in predominantly urban areas prior to 2016. [3][4][5] By collecting data after the introduction of the new Access and Waiting Time Standard, 1 we were able to evaluate the effects of these changes in existing EIP services, such as CAMEO, and anticipate further challenges and opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…What little is so far known has been gathered from services already offering a broader EIP service in predominantly urban areas prior to 2016. [3][4][5] By collecting data after the introduction of the new Access and Waiting Time Standard, 1 we were able to evaluate the effects of these changes in existing EIP services, such as CAMEO, and anticipate further challenges and opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms previous evaluations in early-adopter services, which suggested that patients over the age of 35 would make up a significant proportion of referrals, ranging from 25 to 33%. [3][4][5] A higher proportion of patients over the age of 35 were referred from secondary and acute care in comparison with those aged under 35; the over-35s were more likely to have existing mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delusions (Freeman et al, 2015), anxiety (Naeem et al, 2006) and depression (Sensky et al, 2000) in psychosis have also improved. Benefits have been seen for negative symptoms in CBTp studies compared to treatment as usual but with one exception (Sensky et al, 2000) not against active controls (Lasalvia et al, 2017). Beck and colleagues however have successfully reduced negative symptoms (Grant et al, 2012) using techniques to improve self-defeating attitudes linked to graded activity scheduling.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%